Pertumbuhan dan Hasil Tanaman Kedelai dengan Rhizobacteria Pemacu Pertumbuhan Tanaman dan Pupuk Organik Cair - Adnan, Achmad; Priyadarshini, Rossyda; Purwadi, Purwadi (BIOEDUSCIENCE, 2024)
Background: Many organic wastes are currently used as organic fertilizers. Giving organic fertilizer to plants has a very good impact on soil and plants. The combination of LOF and PGPR can certainly increase the growth and production of soybean plants.  This research was conducted in Tanjung Sari Village, Rembang, Central Java from November 2021 to January 2022. Analytical activities were carried out at the Land Resources Laboratory, Faculty of Agriculture, National Development University "Veteran" East Java. Method: This research method uses a factorial Completely Randomized Design (CRD) consisting of 9 treatments 3 replicates so that 27 experimental units are obtained. The first factor is PGPR (A), namely A0: Without PGPR A1: Banana Bark, A2: Bamboo Root and the second factor is LOF (B), namely B0: Without LOF B1: Banana stem B2: Bamboo shoots. Result: The results of this study showed that the combination of PGPR + LOF treatments made from local raw materials was effective in helping the growth of soybean plants obtained by the combination A2B2 (PGPR bamboo root + LOF bamboo shoot) with the number of pods 36 pods, and plant height 56.60cm, in terms of c-organic analysis (3.05%), N (0.63%), P (15.37%), K (1.23%). This combination is best because it contains lignocellulase enzyme and growth regulators. Conclusion: The combination of PGPR + local raw material-based LOF is effective in enhancing the growth of soybean plants.